A benchmark simulator for quality-by-design and quality-by-control studies in continuous pharmaceutical manufacturing ‒ Intensified filtration-drying of crystallization slurries. (July 2022) - Destro, Francesco; Nagy, Zoltan K.; Barolo, Massimiliano
Highlights: ContCarSim: benchmark simulator of continuous carousel for filtration/drying of slurries. Dynamic mathematical modeling framework validated with experiments on pilot unit. User can implement new control strategies in the simulator. Proposed quality-by-design and quality-by-control challenges for ContCarSim . Sample case study demonstrates simulator features at open-loop and at closed-loop. Abstract: This article introduces ContCarSim, a benchmark simulator for the development and testing of quality-by-design and quality-by-control strategies in the continuous intensified filtration-drying of paracetamol/ethanol slurries on a novel carousel technology, developed by Alconbury Weston Ltd (United Kingdom). The simulator is based on a detailed mechanistic mathematical modeling framework, and has been validated with filtration and drying experiments on a prototype equipment. A set of design- and control-relevant challenges to be addressed through ContCarSim are proposed. A case study is developed, to demonstrate the features of the simulator and its suitability to design, test and optimize the unit operation. ContCarSim is expected to promote the transition to end-to-end continuous pharmaceutical manufacturing and the adoption of closed-loop quality control by the pharmaceutical industry. The simulator can also be employed as a benchmark for data analytics and process monitoring studies.